Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 2323362 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Sitta whiteheadi Sharpe, 1884, Tetraogallus caucasicus (Pallas, 1811), Buteo buteo (Linnaeus, 1758), Ichthyaetus audouinii (Payraudeau, 1826), Cuculus saturatus Blyth, 1843, Crex crex (Linnaeus, 1758), Cinclus cinclus (Linnaeus, 1758), Tringa nebularia (Gunnerus, 1767), Melanocorypha leucoptera (Pallas, 1811), Pluvialis squatarola (Linnaeus, 1758), Serinus canaria (Linnaeus, 1758), Calidris ferruginea (Pontoppidan, 1763), Tringa stagnatilis (Bechstein, 1803), Branta canadensis (Linnaeus, 1758), Saxicola torquatus (Linnaeus, 1766), Tetrao urogallus Linnaeus, 1758, Chlidonias hybrida (Pallas, 1811), Gallinula chloropus (Linnaeus, 1758), Chrysolophus amherstiae (Leadbeater, 1829), Calidris maritima (Brunnich, 1764), Charadrius alexandrinus Linnaeus, 1758, Charadrius asiaticus Pallas, 1773, Motacilla citreola Pallas, 1776, Phylloscopus humei (W.E.Brooks, 1878), Pelecanus rufescens Gmelin, 1789, Branta ruficollis (Pallas, 1769), Circaetus gallicus (Gmelin, 1788), Hieraaetus pennatus (Gmelin, 1788), Numida meleagris (Linnaeus, 1758), Acrocephalus palustris (Bechstein, 1798), Acrocephalus arundinaceus (Linnaeus, 1758), Lanius cristatus Linnaeus, 1758, Pluvialis apricaria (Linnaeus, 1758), Cyanopica cooki Bonaparte, 1850, Phylloscopus griseolus Blyth, 1847, Phylloscopus plumbeitarsus Swinhoe, 1861, Poecile palustris (Linnaeus, 1758), Accipiter gentilis (Linnaeus, 1758), Iduna pallida (Hemprich & Ehrenberg, 1833), Apus affinis (J.E.Gray, 1830), Himantopus himantopus (Linnaeus, 1758), Circus cyaneus (Linnaeus, 1766), Charadrius morinellus Linnaeus, 1758, Anser brachyrhynchus Baillon, 1834, Pyrrhula murina Godman, 1866, Sitta krueperi Pelzeln, 1863, Sturnus unicolor Temminck, 1820, Pica pica (Linnaeus, 1758), Aquila clanga Pallas, 1811, Aythya fuligula (Linnaeus, 1758), Fringilla coelebs Linnaeus, 1758, Falco eleonorae Gene, 1839, Caprimulgus ruficollis Temminck, 1820, Aquila chrysaetos (Linnaeus, 1758), Anthus spinoletta (Linnaeus, 1758), Colinus virginianus (Linnaeus, 1758), Plegadis falcinellus (Linnaeus, 1766), Pinguinus impennis (Linnaeus, 1758), Sitta neumayer Michahelles, 1830, Xema sabini (Sabine, 1819))", "Country is Denmark", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 2323362 records from 38 constituent datasets: 1045 records from iNaturalist Research-grade Observations. 1 records from NBM birds. 3 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 49 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 6 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 204 records from BirdMap Data - GPS tracking of Storks, Cranes and birds of prey, breeding in Northern and Eastern Europe. 4308 records from Threatened species occurrences, Denmark 1991-2015. 1 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 5 records from LACM Vertebrate Collection. 9 records from Paleobiology Database. 447 records from Observation.org, Nature data from around the World. 1 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 2 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 77 records from Xeno-canto - Bird sounds from around the world. 1 records from Institut Mediterrani d'Estudis Avançats: Colección Osteológica de Aves. 2 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 22095 records from EOD - eBird Observation Dataset. 2200 records from EBCC Atlas of European Breeding Birds. 4 records from Bird collection NTNU University Museum. 7 records from Museum of Comparative Zoology, Harvard University. 2290890 records from DOF - Observations from the Danish Ornithological Society. 3 records from Recoveries of birds ringed by Revtangen Bird Observatory (Southwest Norway), 1936-2018. 2 records from Biologiezentrum Linz. 609 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 48 records from Birds fallen at Danish Lighthouses 1883 through 1939. 1 records from Australian National Wildlife Collection provider for OZCAM. 2 records from BoBO - Botanic Garden and Botanical Museum Berlin Observations. 1 records from Ornithologie Federsammlung - SNSD. 12 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 30 records from Lund Museum of Zoology (MZLU). 5 records from Bioblitz 2013 Copenhagen Denmark. 1 records from Natural History Museum Rotterdam - Specimens. 1 records from Norwegian Species Observation Service. 11 records from Naturalis Biodiversity Center (NL) - Aves. 3 records from RBINS DaRWIN. 1250 records from naturgucker. 10 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 16 records from Animal Sound Archive. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences